Interpreting the degradation mechanism of triclosan in microbial fuel cell by combining analysis microbiome community and degradation pathway. (April 2023) - Liu, Qingliang; Zhu, Jinan; Wang, Lu; Wang, Xianshi; Huang, Zhuangsong; Zhao, Feng; Zou, Jing; Liu, Yulei; Ma, Jun
Abstract: Microbes play a dominant role for the transformation of organic contaminants in the environment, while a significant gap exists in understanding the degradation mechanism and the function of different species. Herein, the possible bio-degradation of triclosan in microbial fuel cell was explored, with the investigation of degradation kinetics, microbial community, and possible degradation products. 5 mg/L of triclosan could be degraded within 3 days, and an intermediate degradation product (2, 4-dichlorophen) could be further degraded in system. 32 kinds of dominant bacteria (relative intensity >0.5%) were identified in the biofilm, and 10 possible degradation products were identified. By analyzing the possible involved bioreactions (including decarboxylation, dehalogenation, dioxygenation, hydrolysis, hydroxylation, and ring-cleavage) of the dominant bacteria and possible degradation pathway of triclosan based on the identified products, biodegradation mechanism and function of the bacteria involved in the degradation of triclosan was clarified simultaneously. This study provides useful information for further interpreting the degradation mechanism of organic pollutants in mixed flora by combining analysis microbiome community and degradation pathway. Graphical abstract: Image 1 Highlights: Biodegradation of triclosan by MFC was achieved. Intermediate degradation product (2, 4-dichlorophen) was further degraded. Microbial composition and degradation pathway of triclosan was co-analyzed. Function of different bacteria involved in the degradation process was clarified.